Phytocannabinoids, neuroprotection and the blood-brain barrier - Stone, Nicole (2021)
The blood brain barrier (BBB) is central to the neurovascular unit (NVU) where it creates a semi-permeable barrier between neuronal tissue and the vascular networks that feed the brain. In neurodegenerative conditions and ischaemic stroke, the BBB becomes compromised and as a result its permeability increases. This not only exacerbates neuronal damage at the site of injury but also causes unwanted extravasation of peripheral immune cells into the brain, fuelling the overactivation of the immune response. Endocannabinoids and phytocannabinoids have both displayed neuroprotective effects, attenuating damage in a range of models including Parkinson’s, Huntington’s, amyloid lateral sclerosis and ischaemic stroke. The current study aimed to investigate the neuroprotective properties of emerging phytocannabinoids; specifically focusing on the BBB and NVU in the context of ischaemic stroke pathophysiology.